2019
DOI: 10.1186/s12978-019-0779-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of risky sexual practice, drug abuse and alcohol consumption in adolescents in Iran: a systematic literature review

Abstract: Background Evidence shows that the prevalence of risky sexual practice, drug abuse, and alcohol consumption behaviors in low and middle income countries such as Iran is not in a favorable condition. Preventive programs against these behaviors in Iran are very rare, and the results are unclear, which may be due to the lack of deeply and systematically understanding of the determinants of these behaviors. Evidence suggests that these behaviors are coincidence. So all of these behaviors were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
(29 reference statements)
1
20
0
2
Order By: Relevance
“…However, a recent study suggests the rising trend of alcohol poisoning through the recent years 47 . Outbreaks of methanol poisoning in Iran have been occurred frequently and have been always a public health concern 48 50 . Our data suggests a sharp rise in methanol poisoning in the first 3 months after the outbreak resulting in high mortality in the total population and specifically among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study suggests the rising trend of alcohol poisoning through the recent years 47 . Outbreaks of methanol poisoning in Iran have been occurred frequently and have been always a public health concern 48 50 . Our data suggests a sharp rise in methanol poisoning in the first 3 months after the outbreak resulting in high mortality in the total population and specifically among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The variables of economic and social statuses, the experience of schools' principals, and the presence of counselors were not signi cant, and other studies could not establish a relationship between these variables and bullying, which is in line with the results of our study. Furthermore, it was shown that family can have great effects on controlling and preventing high-risk bullying behaviors, and by educating parents, this behavior can be prevented to some extent (35,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adolescents whose parents rarely understood their problems were more likely to use substances. Previous studies demonstrated that parents' supervision of adolescents reduces substance use practice [27,43]. Limited parental monitoring, involvement, and active substance use in the home at the family level may predispose adolescents to use substances [44].…”
Section: Plos Onementioning
confidence: 99%